What matters in the transition from school to vocational training in Germany : Educational credentials, cognitive abilities or personality? - Protsch, Paula [Verfasser]; Dieckhoff, Martina [Verfasser] (My University, 2011)
"The German multi-tiered school system functions as an institutional mechanism which prevents students from certain social class backgrounds from fulfilling their individual learning potential. Their cognitive abilities are not transformed into corresponding school performances and credentials. Against this backdrop, we ask whether the transition from school to vocational training may enable young people with intermediate and those with lower secondary school degrees to demonstrate their cognitive abilities irrespective of school certificates. We further aim to scrutinise the role of personality traits (Big Five) during the transition process. The analyses based on the German Socio-Economic Panel show - in line with previous research - that type of school degree is crucial in the transition process: Those with intermediate school degrees have faster transitions than those with lower degrees. Moreover, our findings suggest that the relative impact of credentials, cognitive abilities, and personality on labour market success cannot be answered universally. Instead, the relevant mechanisms appear to vary substantially by type of school degree." (Autorenreferat, BIBB-Doku)
Keywords: P 2.1 Schulabgänger; G 1.3.2.2.1 Erste Schwelle, in Ausbildung; T 3.5 Statistik; Schulabgänger; Schulabschluss; Berufseinmündung; Erste Schwelle; Ausbildungsbetrieb; Bewerberauswahl; Einflussfaktor; Empirische Untersuchung; Sozioökonomisches Panel